Cardiovascular Damage in Alzheimer Disease: Autopsy Findings From the Bryan ADRC. Issue 2 (30th June 2005) - Corder, Elizabeth H.; Ervin, John F.; Lockhart, Evelyn; Szymanski, Mari H.; Schmechel, Donald E.; Hulette, Christine M.
Abstract : Autopsy information on cardiovascular damage was investigated for pathologically confirmed Alzheimer disease (AD) patients (n = 84 ) and non-AD control patients (n = 60 ). The 51 relevant items were entered into a grade-of-membership model to describe vascular damage in AD. Five latent groups were identified "I: early-onset AD, " "II: controls, cancer, " "III: controls, extensive atherosclerosis, " "IV: late-onset AD, male, " and "V: late-onset AD, female." Expectedly, Groups IV and V had elevated APOE ε 4 frequency. Unexpectedly, there was limited atherosclerosis and frequent myocardial valve and ventricular damage. The findings do not indicate a strong relationship between atherosclerosis and AD, although both are associated with the APOE ε 4 . Instead, autopsy findings of extensive atherosclerosis were associated with possible, not probable or definite AD, and premature death. They are consistent with the hypothesis that brain hypoperfusion contributes to dementia, possibly to AD pathogenesis, and raise the possibility that the APOE alleleε 4 contributes directly to heart valve and myocardial damage.